Glutamine Antagonist GA-607 Causes a Dramatic Accumulation of FGAR which can be used to Monitor Target Engagement - Alt, Jesse; Gori, Sadakatali S; Lemberg, Kathryn M; Pal, Arindom; Veeravalli, Vijayabhaskar; Wu, Ying; Aguilar, Joanna M H; Dash, Ranjeet P; Tenora, Lukáš; Majer, Pavel; Sun, Qi; Slusher, Barbara S; et al. (Current drug metabolism, 2021)
BACKGROUND: Metabolomic analyses from our group and others have shown that tumors treated with glutamine antagonists (GA) exhibit robust accumulation of formylglycinamide ribonucleotide (FGAR), an intermediate in the de novo purine synthesis pathway. The increase in FGAR is attributed to the inhibition of the enzyme FGAR amidotransferase (FGAR-AT) that catalyzes the ATP-dependent amidation of FGAR to formylglycinamidine ribonucleotide (FGAM). While perturbation of this pathway resulting from GA therapy has long been recognized, no study has reported systematic quantitation and analyses of FGAR in plasma and tumors. OBJECTIVE: Herein, we aimed to evaluate the efficacy of our recently discovered tumor-targeted GA prodrug, GA-607 (isopropyl 2-(6-acetamido-2-(adamantane-1-carboxamido)hexanamido)-6-diazo-5-oxohexanoate), and demonstrate its target engagement by quantification of FGAR in plasma and tumors. METHODS: Efficacy and pharmacokinetics of GA-607 were evaluated in a murine EL4 lymphoma model followed by global tumor metabolomic analysis. Liquid chromatography-mass spectrometry (LC-MS) based methods employing the ion-pair chromatography approach were developed and utilized for quantitative FGAR analyses in plasma and tumors. RESULTS: GA-607 showed preferential tumor distribution and robust single-agent efficacy in a murine EL4 lymphoma model. While several metabolic pathways were perturbed by GA-607 treatment, FGAR showed the highest increase qualitatively. Using our newly developed sensitive and selective LC-MS method, we showed a robust >80- and >10- fold increase in tumor and plasma FGAR levels, respectively, with GA-607 treatment. CONCLUSION: These studies describe the importance of FGAR quantification following GA therapy in cancer and underscore its importance as a valuable pharmacodynamic marker in the preclinical and clinical development of GA therapies.
Keywords: cancer; purine synthesis; Glycine; biomarkery farmakologické; Glutamine antagonist; ribonukleotidy; Biomarkers, Pharmacological; Metabolic Networks and Pathways; Mass Spectrometry; Mice; Glutamine; LC-MS.; formylglycinamide ribonucleotide; vyvíjení léků; Biomarkers, Tumor; Neoplasms; biomarker; nádorové biomarkery; Drug Development; zvířata; nádory; chromatografie kapalinová; formylglycinamidine ribonucleotide; myši; glutamin; glycin; Ribonucleotides; metabolické sítě a dráhy; Chromatography, Liquid; hmotnostní spektrometrie; Animals